The Effectiveness Of Snakes Ladder Games In Increasing Children's Knowledge And Attitudes Regarding Reproductive Health - Reny Mareta Sari; Nurwijayanti; Hera Aviyuni (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
Childhood is the very vulnerable period since children have to depend on their basic need and decision making. Nevertheless, there are many children who cannot get care from their parents or family due to various reasons therefore they are sent to orphanages. Thus, health education for children is something that needs to be given to them. This study aims to analyze the effect of snakes and ladders game on the level of knowledge and attitudes of children about reproductive health. This research is an experimental study conducted on 30 orphanage children using purposive sampling. The intervention is snakes and ladders game. Before and after the intervention, children's level of knowledge and attitudes about reproductive health was measured. Data collection was carried out using pre-test and post-test questionnaires. The statistical analysis showed that there were significant differences in the level of knowledge (p-value: 0.000) and attitude (p-value: 0.001) before and after the intervention. The snake and ladder game are able to increase children's knowledge and attitudes about reproductive health.